APPLICATION OF INTERESTS AND PERFORMANCE IN EDUCATION AND TRAINING MANAGEMENT, AS WELL AS THEIR EFFECT ON WORK PRODUCTIVITY - Handy Suryadi; Muhammad al azhary; Anoesyirwan Moeins (Dinasti Publisher, 2021)
The purpose of this study is as follows: (1) Knowing the evaluation of the performance of the implementation of educational and training programs based on the analysis of interests and performance, so that the results of the review can provide input to the company about activities that must be improved (concentrate here), maintained (keep up good work), have low priority ( low priority ), and the possibility of excessive (possible overkill). (2) Know the level of influence of the implementation of existing education and training programs on employee work productivity. Based on the data processing results, it is known that the elements of the implementation of education and training programs that must be considered and improved are as follows: Training Materials, Non-Formal Education, Training Schedule, Instructor Friendliness, Training Variations, Training Methods, and Training Manuals. While the elements of the implementation of education and training programs that must be maintained are as follows: Formal Education, Instructor Expertise, Instructor Ability, Training Infrastructure Facilities, Training Curriculum, Training Evaluation. The implementation of education and training programs affects employee work productivity, and the implementation of training programs is more dominant. This is because the implementation of training programs is more often done and more applicable, although it still seems theoretical on the employee's work. Therefore, the proper education and training programs will impact increasing the productivity of their employees.